A retrospective UK referendum on the Lisbon Treaty? David Cameron and the big fight - Roderick Parkes (Stiftung Wissenschaft und Politik (SWP), 2008)
For the eventuality that the EU-wide ratification process will still be open when his party comes to power, the leader of the main British opposition party, David Cameron, has promised to hold a referendum on the Lisbon Treaty. The Conservative leadership has even hinted that it would hold a retrospective referendum were the party to come to power after ratification has been completed. Following on the tail of the Irish 'no', these developments will lead some EU leaders to re-evaluate their commitment to the Lisbon Treaty. Thanks to his eurosceptic ideology, they reason, Cameron will prove immune to international pressure and will do his utmost to scupper the Treaty. Yet, a closer examination suggests that, although Cameron faces very real ideological constraints from within his own party, he is ready to proceed in a most non-ideological fashion: Cameron will pragmatically exploit these party-political constraints in order to wring concessions from the UK's EU partners
Keywords: 320